2018
DOI: 10.1016/j.celrep.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Effects of Anti-cancer Drugs and Cancer-Associated Fibroblasts by On-Chip Reconstitution of Immunocompetent Tumor Microenvironments

Abstract: Highlights d A complex HER2 + breast cancer ecosystem is reconstituted and quantitatively described d The effects of the drug trastuzumab (Herceptin) are directly visualized ex vivo d Trastuzumab promotes long cancer-immune interactions and an ADCC immune response d Trastuzumab and CAFs have antagonist immunomodulation effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 43 publications
1
131
0
Order By: Relevance
“…Therefore, if TILs indicate the presence of an immune response, it may be possible that the role of immune surveillance for tumor control is relatively ineffective when using trastuzumab due to stromal reactivity which exerts immune suppression . In support of this possibility are the findings of several recent preclinical studies that demonstrated that CAFs have immunosuppressive effects which may affect the response to trastuzumab . The application of data from a prospective, rigorously conducted randomized clinical trial strengthens the relevance of our observation and highlights the importance of the role of the tumor microenvironment in the efficacy of trastuzumab.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Therefore, if TILs indicate the presence of an immune response, it may be possible that the role of immune surveillance for tumor control is relatively ineffective when using trastuzumab due to stromal reactivity which exerts immune suppression . In support of this possibility are the findings of several recent preclinical studies that demonstrated that CAFs have immunosuppressive effects which may affect the response to trastuzumab . The application of data from a prospective, rigorously conducted randomized clinical trial strengthens the relevance of our observation and highlights the importance of the role of the tumor microenvironment in the efficacy of trastuzumab.…”
Section: Discussionsupporting
confidence: 71%
“…S1). Given that preclinical data suggested that reactive stroma may decrease trastuzumab efficacy, we investigated this hypothesis in HER2‐positive breast cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4e, right). To go deeper in the characterization of BC cell motility in 3D, we took advantage of the tumor-on-chip system 42 , a microfluidic device where cancer cells and CAF subsets were co-cultured in 3D and followed by time-lapse video microscopy. In this system, we reproduced the intrinsic CAF subset motility, CAF-S1 being more motile than CAF-S4 ( Supplementary Fig.…”
Section: Caf-s1mentioning
confidence: 99%
“…Most cancer cells utilize the extracellular matrix (ECM), which acts as a physical constraint, to mediate communication signals, promote interactions with other cells and establish the cancer microenvironment [5][6][7][8]. Cancer microenvironments are mainly constituted by cancer-associated fibroblasts (CAFs), macrophages, mesenchymal stem cells and cancer-specific ECM [9].…”
Section: Introductionmentioning
confidence: 99%